In vivo and in vitro aging of common carp Cyprinus carpio sperm after multiple hormonal application and stripping of males - Zhang, Songpei; Cheng, Yu; Linhartová, Zuzana; Rodinová, Vladimíra; Shazada, Nururshopa Eskander; Wu, Qing; Linhart, Otomar (Fish physiology and biochemistry, 2022)
The present study was designed to evaluate sperm phenotypic variables during in vivo and in vitro storage following multiple sperm stripping in common carp (Cyprinus carpio L.). Each male was injected 3 times with carp pituitary 3 days apart. Sperm was stored in vivo in the body cavity for 0.5 days (Fresh sperm) and 3 days (Old sperm) after hormonal stimulation. Then sperm was collected and diluted with a carp extender at a ratio of 1:1, and stored in vitro on ice for 0, 3, and 6 days. The phenotypic parameters, including the number of total motile spermatozoa, number of fast motile spermatozoa, number of motile spermatozoa, percentage of fast motile spermatozoa, and percentage of spermatozoa motility were the major components of principal component analysis (PCA). In general, Fresh sperm from the first stripping showed slightly better quality than Old sperm from the second and third stripping, especially in the phenotypic parameters of a number of total spermatozoa and a number of total motile spermatozoa (P < 0.05). The highest kinetic and quantitative spermatozoa variables were obtained in Fresh and Old sperm just after sperm collection (0-day storage in vitro), and then they were decreased during the period of in vitro storage up to 6 days (P < 0.05). However, the fertilization, hatching, and malformation rates from Fresh sperm were similar compared with the Old sperm. Sperm could be stripped 0.5 days post hormonal treatment and stored in vitro up to 6 days with good fertilization performance (fertility, hatching, and malformation rates were 92.5%, 91.5%, and 1.3%, respectively). Therefore, our results suggested that multiple hormonal treatments with multiple stripping could be used in artificial reproduction in common carp.
Keywords: Semen Preservation; Spermatozoa aging; kapři; Cryopreservation; Aging; Animals; Male; Carps; Spermatozoa; Sperm Motility; Common carp; kryoprezervace; motilita spermií; In vivo; sperma; mužské pohlaví; Sperm storage; uchování spermatu; In vitro; stárnutí; zvířata; Semen; spermie; led; Ice